Barriers to compliance with the use of free-of-cost spectacles prescribed through door-to-door screening of children in urban slums of Delhi - Vaisakhi Prasannan; Shalinder Sabherwal; Shailja Tibrewal; Zeeshan Siddiqui; Atanu Majumdar; Suma Ganesh (Indian Journal of Ophthalmology)
Purpose: Compliance with spectacles provided during school eye-screening programs has been low. The aim of this study was to assess compliance to free-spectacles provided to children via a door-to-door screening model and to ascertain the reasons for non-compliance. Methods: A cross-sectional study was conducted, including children aged 5–18 years, 3–6 months after spectacle prescription; vision screeners assessed compliance during unannounced visits via direct observation and parental enquiry. Full compliance was defined when a child was wearing spectacle at the time of visit, taking spectacles to school, and using them for ≥4 hours/day at home. Qualified compliance was considered if two of the above criteria were met, and non-compliance as one or no criteria met. Parents’ and children’s reasons for non-compliance were recorded using a mixed-type questionnaire, and spectacle quality was assessed. The association of compliance with age, gender, spectacle quality, parental education and occupation, parents’ or siblings’ use of spectacles, uncorrected visual acuity (UCVA), best corrected visual acuity, improvement of VA, and magnitude and type of refractive error was analyzed. Results: A total of 436 children, including 189 (43.3%) males, were included in the study. Full compliance, qualified compliance, and non-compliance were observed in 297 (68.1%), 34 (7.8%), and 105 (24.1%) children, respectively. Common reasons for non-compliance were unsatisfactory vision with the spectacles, dislike for the frames, watering eyes, and headache. Factors affecting compliance included spectacle quality, distance UCVA in the worse eye, father’s education, and mothers’ occupation. Conclusion: Compliance to spectacles in a door-to-door screening model was 76%. Quality of the spectacles was the most important determinant of compliance.